Contributions of the digital photogrammetry and 3D modelling of Roman inscriptions to the reading of damaged tituli: An example from the Hispania Tarraconensis (Castiliscar, Saragossa). (March 2019) - Andreu, Javier; Serrano, Pablo
Abstract: Over the past few years, digital photogrammetry has not only been used increasingly more for documenting archaeological remains but also as a means of obtaining 3D data from epigraphic documents, in general, and Roman ones, in particular. These models, in addition to serving to disseminate epigraphic material and to further collaborative work, have opened up possibilities for improving the reading of damaged inscriptions. Thus, this study describes an action protocol, based on image treatment techniques and replicable in other similar cases, deriving from the 3D modelling of a Roman funerary stele from Castiliscar (Saragossa, Spain).